Heavy ion beam probe design study for TCABR - Chmyga, A.A.; Deshko, G.N.; Dreval, N.B.; Khrebtov, S.M.; Komarov, A.D.; Kozachek, A.S.; Krupnik, L.I.; Melnikov, A.V.; Perfilov, S.V.; Galvao, R.M.O.; Kuznetsov, Yu.K. (Вопросы атомной науки и техники, 2003)
The Heavy Ion Beam Probe (HIBP) diagnostic is known as a unique tool for the direct plasma electric potential measurements. It gives also information on plasma density, temperature and current profile. The method is based on the injection of single charged ion beam into the plasma and the registration of the double charged particles born due to collisions with the plasma electrons. The area of the ionization in plasma is the sample volume of the plasma potential measurements. The position and the size of the sample volume are determined by the calculation of the trajectories of the probing particles. Three schemes have been analysed: Cs⁺, Tl⁺ ion and neutral injection for TCABR parameters: B0 = 1.5 T, Ipl = 135 kA. The calculations show that ion probing allows getting radial profiles of TCABR plasma parameters with the injection angle fast scan system. In all cases of ion beam injection we must use a curved beam line for ion beam transportation from last  steering plates towards upper port. The primary ion beam injector must be situated out of high magnetic field area and its length is about 1.5m. The energy range (less than 100 keV for Cs⁺, or Tl⁺) allows using compact and cheap ion gun equipmen Система зондування плазми пучком важких іонів відома як унікальний інструмент для прямих вимірювань потенціалу плазми. Вона також дозволяє одержувати інформацію про густину плазми, температуру і профіль току. Метод заснований на інжекції пучка однозарядних іонів у плазму та реєстрації двозарядних часток, утворених у результаті зіткнень з електронами плазми. Область іонізації у плазмі визначає елементарний об’єм, у якому здійснюється вимірювання потенціалу плазми. Положення і розмір елементарного об’єму визначається за допомогою розрахунків траєкторій зондуючих часток. Проаналізовано три варіанти: інжекція іонів Cs⁺, Tl⁺ та нейтральних атомів для параметрів TCABR: B0 = 1.5 T, Ipl = 135 кA. Розрахунки показують можливість одержання профілів параметрів плазми TCABR за допомогою системи швидкого сканування по кутам інжекції іонного пучка. У всіх випадках інжекції іонного пучка необхідно застосування вигнутого іонопроводу для транспортування іонного пучка від вихідних відхиляючих  пластин до порту токамака. Інжектор первинного іонного пучка повинен бути розташований поза областю сильного магнітного поля , а його довжина буде біля 1,5 м. Енергія іонного пучка (біля 100 кеВ для Cs⁺ або Tl⁺) дозволяє застосувати компактний и дешевий іонний інжектор. Система зондирования плазмы пучком тяжелых ионов известна как уникальный инструмент для прямых измерений потенциала плазмы. Она так же позволяет получать информацию о плотности плазмы, температуре и профиле тока. Метод основан на инжекции пучка однозарядных ионов в плазму и регистрации двухзарядных частиц, образующихся в результате столкновений с электронами плазмы. Область ионизации в плазме определяет элементарный объем, в котором происходит измерение потенциала плазмы. Положение и размер элементарного объема определяются с помощью расчета траекторий зондирующих частиц. Проанализировано три варианта: инжекция ионов Cs⁺, Tl⁺ и нейтральных атомов для параметров TCABR: B0 = 1.5 T, Ipl = 135 kA. Расчеты показывают возможность получения профилей параметров плазмы TCABR с помощью системы быстрого сканирования по углу инжекции ионного пучка. Во всех случаях инжекции ионного пучка необходимо использование изогнутого ионопровода для транспортировки ионного пучка от выходных отклоняющих  пластин до порта токамака. Инжектор первичного ионного пучка должен быть расположен вне области сильного магнитного поля , а его длина составит около 1,5 м. Энергия ионного пучка (около 100 кэВ для Cs⁺ или Tl⁺) позволяет использовать компактный и дешевый ионный инжектор.